A quantitative risk assessment methodology based on CCDF risk curve for accidental releases from fusion reactors. (December 2020) - Wang, Zhen; Chen, Shanqi; Ge, Daochuan; Chen, Chao; Chen, Zhibin
Highlights: The accident characteristics of fusion reactors was comprehensively analyzed. A quantitative risk assessment methodology for fusion accidents was developed. A societal risk indicator based on CCDF risk curve for fusion accidents was proposed. Abstract: Fusion reactors are expected to be more safe and environmentally friendly in the development of nuclear energy systems. It is vital to fully understand the overall radiation risk level of fusion reactors in comparison with existing nuclear energy systems. The objective of this paper is to propose a risk assessment methodology for fusion reactor accidents, which is capable of quantifying the risk level comparable to other advanced nuclear energy systems. In this paper, fusion specific accident characteristics are comprehensively analyzed in comparison with ITER and fission reactors. The postulated initiating events as well as possible environmental release routes are also presented for DEMO, and then deterministic risk assessment is applied to design basis accidents, while the coupling of deterministic risk assessment and probabilistic risk assessment is suggested for design extension conditions. The societal risk of DEMO is proposed to be presented by a Complementary Cumulative Distribution Function (CCDF) risk curve.